A Third Gender in South Africa: Does the legal non-recognition of a third gender violate non-binary transgender person's Constitutional rights to dignity and equality? - Sloth-Nielsen, Rachel (Department of Public Law, 2020)
This dissertation will attempt to answer question whether, in terms of the right to dignity in s10 and the prohibition of unfair discrimination in s9 of the South African Constitution, the State must recognise in law a third gender for transgender individuals who do not identify as either male or female. It does so, first, by asking whether the failure by the state to provide for the legal recognition of a third gender violates transgender person's right to dignity. Second, the enquiry proceeds to discuss whether s9(3) of the Constitution (which prohibits unfair discrimination on any ground, including on the listed grounds of sex, gender and sexual orientation) requires the state to recognise a third gender. After discussing the lived experiences of transgender persons in South Africa, the thesis reviews the terminology and concepts relevant to this area of study, in order to lay the foundation for the subsequent examination of relevant case law, the Constitutional Court's approach to dignity, and the analysis of the application of s(9)(3). I submit that transgender persons fall within the Constitutional Court's definition of a vulnerable group in that they have suffered past patterns of disadvantage, they constitute a minority in South Africa and are subject to stereotyping and bias. Despite the Constitutional Courts erroneous pronouncement that transsexualism falls under the umbrella of sexual orientation, it is argued, rather, that since the expression of their gender identity by gender nonconforming persons shares many of the characteristics of the specified grounds listed in s9(3), unfair discrimination can be found on a ground analogous to those grounds listed in the Constitution. The failure to allow for recognition of a third gender is thus under-inclusive. It cannot be justified under the limitations analysis. Further, if objections were to be raised by the state that recognition is not feasible or affordable and is, hence, justified, I conclude that because there are ways to accommodate individuals who do not identify as binary which are not unduly taxing on the State, this argument would fail.